Eksplorasi potensi budi daya lebah madu Apis cerana Fabricius di Taman Kehati Kiarapayung, Jawa Barat: Exploration of the potential of Apis cerana Fabricius beekeeping in the Kiarapayung Biodiversity Park, Jawa Barat - Asfiya, Wara; Winara, Aji; Prativi, Mahensa Billqys Nurhayati; Ruswandi, Agus; Narakusumo, Raden Pramesa; Encilia; Sumadijaya, Alex; Kahono, Sih; Darmawan; Sarino; Budiasih, Yulie; Hapsari, Laras Ay (Jurnal Entomologi Indonesia, 2025)
This study examines the potential for rearing Apis cerana Fabricius honey bees in Taman Kehati Kiarapayung, West Java. Observations were conducted by installing 39 beehive in various locations and observing the flora that serve as bee food sources. A total of 50 plant species from 24 families were identified as bee food sources. Out of the 39 beehive, only 4 were successfully inhabited by bee colonies, showing a success rate of 10.3%. The observed colony growth ranged from 3 to 9 honey combs per hive. The main challenges in cultivation are the decrease in food availability during the dry season with very low rainfall, and pest disturbances such as wax moths (Galleria mellonella), wasps (Vespa sp.), and ants (Formicidae). The results of this study indicate that A. cerana beekeeping has the potential to be implemented in specific locations with sufficient food availability and effective pest management. This potential can serve as an additional source of income for the local community and support environmental conservation efforts by utilizing biological resources and biodiversity in a non-destructive manner at conservation sites.